A novel pathway to recover hydrocarbons from polyethylene residues through the combustion-driven pyrolysis process - Duque, João Vitor Ferreira (2021)
Global production of plastic materials has grown drastically, but the technologies adopted by industry and the policies of combining waste streams, collection, treatment, and disposal have not followed this rapid growth rate. Several methods of thermochemical conversion of plastic waste into useful products have been investigated in the last decades; however, in terms of energy efficiency, the search for a technique that results in the recovery of noble products from plastic wastes is still a challenge, as is the understanding of its thermal degradation behavior. Therefore, the thesis’s general objective was to develop a self-sustainable energy device that uses low-grade fuels as heat-drive to pyrolysis, perform the polyethylene waste thermal cracking, and recover an energy-dense material. The steps toward achieving these objectives were to characterize a recycled polyethylene waste to determine its molecular composition and kinetics pathway from a single-step to a multi-step perspective; to launch a novel device in which the input energy for pyrolysis is driven by a combustion front propagating in a porous matrix, at this step, a new methodology was established to obtain a longitudinal temperature profile (LTP) for reactors with temperature increasing with time; to describe quantitatively and qualitatively for the first time, the propagation of a smoldering front in annular space - through temperature in time, gas analysis, and LTP - that wraps a concentric cylinder chamber in which the heat released by the combustion front is transferred for waste conversion; and finally, to conduct experiments toward the production and recovering of an energy-dense pyrolysis product in the form of wax and to characterize the wax employing FTIR to identify the functional groups, and a detailed kinetic analysis. The research results show that the polyethylene undergoing thermal and mechanical stress in its cycle life has functional groups with long carbon chains while weakening the compounds’ bonds. The main consequence was that recycled polyethylene need less activation energy to degrade thermally, modifying the pyrolysis pathway’s chemical groups. The designed combustion-driven reactor (C-DPyR) could perform polyethylene plastic waste pyrolysis. The proposed LTP served to explore the heat inputted to the pyrolysis chamber, ratifying that a self-sustaining combustion process carried enough energy to supply pyrolysis. The index Energy Availability showed that in the worst case, it remains 11% of energy underused, and at higher thermal energies conditions, just about 5% of the energy is consumed to convert the plastics. The primary outcome was that the volume ratio energy from combustion/energy to pyrolysis could be reduced by increasing the pyrolysis chamber’s volume to convert more kg of plastic per batch. The conclusion can also be drawn that different heat inputs were used to pyrolyze the polyethylene waste, resulting in different pyrolysis products’ yields. A maximum of about 87 wt.% of wax was recovered from an experiment at low thermal energy, confirming that low-grade fuel combustion is an alternative heat source capable of pyrolyzing plastic waste. The enthalpies of the recovered products hovered around 2115 J/g, and according to FTIR results, the wax’s functional groups identified were like the ones in low-density polyethylene’s waste. Therefore, the operational conditions attained by C-DPyR were able to recover a polyethylene wax. That means the C-DPyR process has the potential benefits of feedstock recycling in plastic waste management.